Hydrothermal Synthesis, Physical Characterization and Fluoride Adsorption of TiO2/CeO2 - Wu, J.; Zhou, L.; Chen, L.; Zhao, J. (Asian Journal of Chemistry, 2012)
Novel porous fluoride adsorbents were synthesized by co-doping CeO2 and TiO2 using hydrothermal method in the presence of the P123 (EO20PO70EO20) as template. The physical properties of these resulting materials were characterized by X-ray diffraction, scanning electronic microscope and nitrogen adsorption/desorption isotherms and the results revealed that the materials had high surface area, uniformity in the ordered porous structure. The adsorption characteristics of fluoride on synthesized materials were studied using batch methods. The results showed that the adsorption isotherms on these adsorbents were correlated with the Langmuir and Freundlich adsorption equations and the adsorption capacity depended on contact time, initial fluoride concentration and adsorbents concentration, etc. The TiO2/CeO2 (1:1) exhibited the strongest adsorption capacity in all synthesized materials.